Pengaruh Early Mobilization Terhadap Kekuatan Otot Dan Tingkat Nyeri Pada Pasien Post Operasi Orif Di RSUD Karsa Husada Batu - Tyo Herfindo Putra; Marsaid, Marsaid; Astuti, Erlina Suci; Yuliwar, Roni (Jurnal Keperawatan Muhammadiyah, 2026)
ABSTRACT Objective: The number of patients undergoing fracture surgery with Open Reduction and Internal Fixation (ORIF) continues to increase each year, accompanied by postoperative complications such as pain, decreased muscle strength, and limited mobility. Early mobilization is considered an effective intervention to prevent these complications. This study aimed to determine the effect of early mobilization on muscle strength and pain reduction in postoperative ORIF patients. Methods: This research employed a quasi-experimental design with a pre- and post-test approach. The sample consisted of 16 patients in each group, selected using the Federer formula. The intervention group received early mobilization and analgesics, while the control group received analgesics only. Muscle strength was measured using the Manual Muscle Testing (MMT) scale, and pain levels were assessed using the Numerical Rating Scale (NRS). Data were analyzed using the Wilcoxon test with a significance level of <0.05. Results: The early mobilization group showed an improvement in muscle strength to level 3 in 68.8% of patients and a significant reduction in pain, with 87.5% of patients reporting mild pain. In contrast, the control group reached only level 2 muscle strength in 87.5% of patients, and only 31.3% experienced mild pain. The p-values were 0.002 for muscle strength and 0.001 for pain level Conclusion: Early mobilization is more effective than standard care in improving muscle strength and reducing pain in postoperative ORIF patients. Failure to implement early mobilization may lead to complications such as joint stiffness, contractures, muscle weakness, and circulatory issues that increase the risk of thrombosis. It is recommended that ward nurses provide education and implement early mobilization interventions in accordance with standard operating procedures.